Great hatred, little room : making peace in Northern Ireland / Jonathan Powell. - Powell, Jonathan, 1947- (Vintage, 2009)
'Great Hatred, Little Room' tells the inside story of how the Northern Ireland peace talks almost came to collapse and how the parties finally, thankfully, reached a deal.